Clinical, metabolic and biochemical responses to a diet and aerobic excercise intervention in early-onset type 2 diabetes mellitus - O'Hanlon, Declan (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2013)
This study was a longitudinal, randomised, controlled trial. Two primary groups of subjects were recruited for comparison: young obese patients (less than 30 years of age) with early- onset type 2 diabetes (YT2), and a control group of body mass index (BMI) matched older patients (>50 years) with later-onset type 2 diabetes (OT2). The study protocol featured a 6 month crossover lifestyle intervention, including a separate 3 month dietary intervention and a 3 month exercise intervention, assigned in random order. The effect of the entire 6 month intervention, the crossover effect, and the effect of the individual 3 month components were all examined.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin